ANALISIS PENGARUH PENGUMUMAN STOCK REPURCHASE TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY PADA SAHAM YANG TERDAFTAR DALAM BURSA EFEK INDONESIA PERIODE 2011-2015 - Chandra Jaya Cahya (Jurnal Bina Manajemen, 2017)
This study aims to analyze the effect of stock repurchase announcements made by 30 companies listed in Indonesia Stock Exchange period 2011-2015 against abnormal return and trading volume activity owned by each share. In conducting this research, researcher used descriptive analysis method that uses the smallest value, largest, average and standard deviation to see the characteristics of abnormal return and the amount of stock volume. Researcher also use statistical analysis by looking at the value of p and t-stats of abnormal return and stock volume. The estimated period used is 120 days before the announcement until4 days before the announcement, while the test period used is 3 days before and 20 days after the announcement. The results show that stock repurchase does not have an effect on abnormal return and trading volume activity. Based on these results, it can be said that the level efficiency of capital market in Indonesia already quite strong. In addition, the research results show that most companies do stock repurchase at the time the Indonesian economy is experiencing a downturn. This is done not to boost stock prices, but only to keep stocks from falling deeper. As long as the economic condition is still unstable and there is no momentum that can make the market lively, then the stock price will be difficult to boost and buyback efforts made by the company will not create a market reaction.